”Att jag kallar mig själv för lärare i fritidshem uppfattar jag skapar en viss provokation”. Om de nya grundlärarna med inriktning mot arbete i fritidshem. - Helena Ackesjö; Ulla Karin Nordänger; Per Lindqvist (Educare)
In 2014 the first cohort of (a newly designed group of teachers) ”primary teachers with a specialization in extended school education” graduated from Swedish universities. In addition to the traditional formal qualifications as leisure pedagogues their degree also includes the competency to teach practical/aesthetical subjects in compulsory school up to year six. The newly designed teachers thus have to relate to dual professional identities and try to maintain balance between their work in the traditional socially oriented recreation centers against their teaching in a goal- and results-driven school. In this article we study a group of 40 new teachers before and after graduation, trying to get hold of how they perceive and negotiate their professional identities and how they orient themselves in the professional landscape. The results show that the graduates try to balance their own ideals and professional intentions against traditional professional identities and labor market conditions.